Bridging Borders in Educational Leadership: Reflections on a Study Abroad Program in South Korea (International Journal of Multidisciplinary Perspectives in Higher Education, 2025)
This paper provides an overview and reflection of a study abroad program in South Korea designed for American students enrolled in a Doctor of Education program in educational leadership. The paper will begin with background information about the study abroad program, followed by details on the study abroad activities and site visits. The paper then outlines key assignments and concludes with major takeaways from the experience.